The impact of viral marketing on consumer’s trust and purchasing decision - Yayuk Mulawati Rohmah; Afif Zaerofi; Rachmawaty Rachmawaty (IDEAS: Journal of Management & Technology, 2021)
This study is aimed at determining the effect implementation of viral marketing on consumer’s trust through Instagram and their impact on consumer’s trust and purchasing decision by consumers in buying halal food. This study uses quantitative approach and survey method. Population of this study was 1.653 students of IAI Tazkia Bogor with 175 students who have an account and have made purchasing through Instagram as samples. To analyze the data, path analysis is used with the help of SPSS 16.00 for windows program. The result of this study suggests that viral marketing has positive and significant impact on both internal and external consumer’s trust. Interestingly, viral marketing, internal and external consumer’s trust simultaneously also have a significat impact on purchasing decision.